Cash flow management on ptptn loan among IPTA Bachelor Degree program students in Sabah and Sarawak / Corina Joseph, Tina Stephen Enggong and Rosmini Mohd Aripin - Joseph, Corina; Stephen Enggong, Tina; Mohd Aripin, Rosmini (UiTM Shah alam, Selangor, 2004)
Perbadanan Tabung Pendidikan Tinggi Nasional (PTPTN) plays an important role in helping students who are unable to pursue studies because of financial problem. Every year, a group of students were identified as the recipient based on certain guidelines. However, majority of them are having financial difficulty due to lack of knowledge on cash management practice. In order to find out the level of cash management practice among them, a study was conducted to identify factors that might affect the level of cash flow management practice among the PTPTN loan recipients. i.e.IPTA undergraduates in Sabah and Sarawak. The data were obtained from questionnaire and were statistically analyzed using SPSS. The analysis of data revealed that majority of the respondents irregularly practised cash management. As a whole, it can be concluded that financial behaviour item such as pay bill on time has significant relationship with gender, university course, location of university, place of students' residence and Bumiputera status. This is followed by items such as keep ATM transaction receipts, save for large purchases, know cost of buying on credit and know about investment which have significant relationship with any 4 determinants. However, there is no significant relationship between self-efficacy item that is confident in making decision about cash flow with all the 5 determinants namely gender, university course, location, place of parents' residence and Bumiputera status. Thus it can be concluded that most of our respondents are risk adverse despite practising irregular cash management practice. Some recommendation has also been made to improve the existing scenario.